2017
DOI: 10.1155/2017/3481710
|View full text |Cite
|
Sign up to set email alerts
|

Triethylenetetramine Synergizes with Pharmacologic Ascorbic Acid in Hydrogen Peroxide Mediated Selective Toxicity to Breast Cancer Cell

Abstract: Breast cancer is characterized by overexpression of superoxide dismutase (SOD) and downregulation of catalase and more resistance to hydrogen peroxide (H2O2) than normal cells. Thus, relatively high H2O2 promotes breast cancer cell growth and proliferation. However, excessive intracellular H2O2 leads to death of breast cancer cells. In cancer cells, high level ascorbic acid (Asc) is able to be autoxidized and thus provides an electron to oxygen to generate H2O2. In the present study, we demonstrated that triet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…Hence, pre-exposure of cancer cells to oxidative agents further increases the oxidative stress of cancer cells, as compared to normal healthy cells. For example, exposure of MCF-7 breast cancer cells with triethylenetetramine (TETA) enhanced the autooxidation of Vitamin C thereby inducing elevated oxidative stress, and H 2 O 2 production, finally leading to cell death (Wang et al, 2017). With particular reference to ascorbic acid, it is known as an antioxidant vitamin and hence, is non-toxic to normal healthy cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, pre-exposure of cancer cells to oxidative agents further increases the oxidative stress of cancer cells, as compared to normal healthy cells. For example, exposure of MCF-7 breast cancer cells with triethylenetetramine (TETA) enhanced the autooxidation of Vitamin C thereby inducing elevated oxidative stress, and H 2 O 2 production, finally leading to cell death (Wang et al, 2017). With particular reference to ascorbic acid, it is known as an antioxidant vitamin and hence, is non-toxic to normal healthy cells.…”
Section: Discussionmentioning
confidence: 99%
“…As the CSCs/TICs are the ones which have survived during the initial chemotherapy, such CSCs/TICs tend to acquire chemoresistance and hence, the patient fails to respond to the same chemotherapeutic drugs after the cancer relapses. Such chemoresistance is attributed to various features of CSCs such as presence of ABC transporter proteins for effluxing the drug (Zhou et al 2001;Lou and Dean, 2007;Hao et al, 2010;Gatti et al, 2011;Shafi and Jabeen, 2017); presence of prosurvival protein BCL2 and associated proteins such as BCL-XL, BCL-W, BCL A1A, MCL-1 (Sinicrope et al 1995;Abdullah and Chow, 2013;Carter et al 2016); altered DNA damage/repair response (Abdullah and Chow, 2013;Yu et al, 2016a;Wang et al, 2016;Wang et al, 2017); and also structural changes in the endocrine receptors (Stender et al, 2017). Hence, 90% of the drug failures in metastatic cancer are due to chemoresistance (Longley and Johnston, 2005;Eduati et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Assanga et al 35 verified the growth curves of tumor and non-tumor cell lines treated with extracts of Phoradendron californicum, evaluating the selectivity index of the extracts in L929 lineage and verified that the extracts were selective to the tumoral ones. Wang et al, 36 Oliveira et al 37 and Moura et al 38 showed that their compounds were selectively toxic to tumor lineages and had lower non-tumor linear toxicity.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…However, when used at pharmacological doses ( ‡20 mM), which can be achieved only through intravenous delivery, its oxidation can deliver a high flux of H 2 O 2 (57,85,279). AA induces apoptosis in osteosarcoma, neuroblastoma, T cell leukemia, breast, pancreas, prostate, and colon cancers (62,133,269,350,355). Combination treatment of AA with several chemotherapy regiments has yielded positive outcomes, including improved efficacy of cisplatin and 5-FU against esophageal cancer (1), increased activity of doxorubicin, cisplatin, and paclitaxel in human breast carcinoma cells (181), synergistically enhancing the cytotoxicity of cisplatin against cervical cancer cells (188), and enhanced arsenic trioxide-induced cytotoxicity in multiple myeloma cells (120).…”
Section: Ascorbic Acidmentioning
confidence: 99%